2007
DOI: 10.1177/0020764007078362
|View full text |Cite
|
Sign up to set email alerts
|

The Harvard Trauma Questionnaire: Adapting a Cross-Cultural Instrument for Measuring Torture, Trauma and Posttraumatic Stress Disorder in Iraqi Refugees

Abstract: The methodology described proved to be a useful approach to developing a trauma measure that is culturally grounded in a multi-dimensional model of mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
175
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(182 citation statements)
references
References 37 publications
3
175
0
4
Order By: Relevance
“…As such, grief scales and other measures predicated on Western norms are likely to lack contextual relevance in different settings. This assertion is consistent with previous research highlighting the importance of cross-cultural adaptation in the measurement of psychological problems including anxiety, trauma and depression (Shoeb, Weinstein, & Mollica, 2007;Sweetland, Bekin, & Verdeli, 2014;Myer et al, 2008).…”
supporting
confidence: 92%
“…As such, grief scales and other measures predicated on Western norms are likely to lack contextual relevance in different settings. This assertion is consistent with previous research highlighting the importance of cross-cultural adaptation in the measurement of psychological problems including anxiety, trauma and depression (Shoeb, Weinstein, & Mollica, 2007;Sweetland, Bekin, & Verdeli, 2014;Myer et al, 2008).…”
supporting
confidence: 92%
“…The questionnaire generates a DSM-IV PTSD score, a Self-perception of functioning score and a total score. Each score ranges from 1-4, and the recommended clinical cut-off is ≥ 2.00 (Shoeb, Weinstein, & Mollica, 2007).…”
Section: Harvard Trauma Questionnaire (Htq)mentioning
confidence: 99%
“…The new DSM-V took these notes seriously and applied the suggested changes in trauma characteristics for PTSD algorithm calculation 41 . A possible explanation for the low PTSD prevalence might be related to the high population resilience which was also implicated in similar studies in Lebanon 8,34 . A recent study using a different tool (Harvard questionnaire) among high risk samples had reported a much higher PTSD rate (43%) among survivors exposed to suicidal explosions in Kerbala city, 12 and in other cities in in Iraq, 13 and in many other studies in Gaza strip and North Ireland 14,15 .…”
mentioning
confidence: 69%
“…One potentially significant social characteristic in these countries concern the extended and large family pattern with strong social support of all family members, relatives and even neighbours for those exposed to trauma. Higher population resilience might be the reasons behind these low rates and could be related to the socio-cultural context in these countries, 8,34,35 however, exploring the exact underlying factors requires further studies. An additional reason behind the low PTSD rate in Iraq might be methodological, related to the stringent significance level used or the high missing symptom answers in this study.…”
mentioning
confidence: 99%